1999
DOI: 10.1074/jbc.274.19.12955
|View full text |Cite
|
Sign up to set email alerts
|

Human CARD4 Protein Is a Novel CED-4/Apaf-1 Cell Death Family Member That Activates NF-κB

Abstract: The nematode CED-4 protein and its human homolog Apaf-1 play a central role in apoptosis by functioning as direct activators of death-inducing caspases. A novel human CED-4/Apaf-1 family member called CARD4 was identified that has a domain structure strikingly similar to the cytoplasmic, receptor-like proteins that mediate disease resistance in plants. CARD4 interacted with the serine-threonine kinase RICK and potently induced NF-B activity through TRAF-6 and NIK signaling molecules. In addition, coexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
294
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(299 citation statements)
references
References 16 publications
(19 reference statements)
3
294
0
Order By: Relevance
“…[25,47e51]. In humans, members of NLRs can coordinate caspaseinduced apoptotic signaling pathways [52,53]. Our previous study showed that overexpression of zebrafish NOD2 had no effect on cell viability when expressed alone.…”
Section: Discussionmentioning
confidence: 99%
“…[25,47e51]. In humans, members of NLRs can coordinate caspaseinduced apoptotic signaling pathways [52,53]. Our previous study showed that overexpression of zebrafish NOD2 had no effect on cell viability when expressed alone.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, instead of being sequestered to membraneassociated Bcl-2 or Bcl-x L , Apaf-1 seems to constitutively reside in the cytoplasm to await the release of cytochrome c for the activation of caspase-9. A novel CED-4 homolog, named Nod1/CARD4 42,43 has recently been identified, and it will be interesting to determine whether it fulfills the criteria to form an apoptosome with Bcl-2 or Bcl-x L . Based on the findings that Bcl-2 and Bcl-x L prevent the release of cytochrome c, it is expected that these proteins bind to and inhibit a CED-4 homolog that functions upstream of mitochondria to initiate the release of cytochrome c and other apoptogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…NOD1 and NOD2 have been cloned from mammals including human beings [14], mice [15] and porcine [16,17]. An examination of the zebrafish genome suggests that mammalian NOD1 and NOD2 orthologs also existed in fish [18,19].…”
Section: Introductionmentioning
confidence: 99%